2019
DOI: 10.3389/fpsyt.2019.00095
|View full text |Cite
|
Sign up to set email alerts
|

Empathy at the Heart of Darkness: Empathy Deficits That Bind the Dark Triad and Those That Mediate Indirect Relational Aggression

Abstract: The dark triad (DT) traits–psychopathy, narcissism and Machiavellianism–have collectively been linked to reduced empathy and increased aggression; however, their association with distinct empathic subtypes remains unclear; and unique links to indirect relational aggression (IRA) have not been delineated. Moreover, whether dark traits should be conceptualized individually, as a dyad or as a triad with a dark core centered around the absence of empathy is debated. The current study examines (i) whether impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 62 publications
2
44
0
4
Order By: Relevance
“…Dark dyad was found to have a positive and significant correlation with social dominance orientation, but showed negative associations with morality and empathy. This is similar to what has been reported by Arvan (2013) and Heym et al (2019), respectively. On the other hand, narcissism showed a non-significant yet positive correlation with morality and empathy, which suggests that narcissists are less devoid of these positive traits than those characterized by dark dyad traits (Miller et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Dark dyad was found to have a positive and significant correlation with social dominance orientation, but showed negative associations with morality and empathy. This is similar to what has been reported by Arvan (2013) and Heym et al (2019), respectively. On the other hand, narcissism showed a non-significant yet positive correlation with morality and empathy, which suggests that narcissists are less devoid of these positive traits than those characterized by dark dyad traits (Miller et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Paulhus, Williams, and Harms (2001) empirically demonstrated that narcissism per se is not a dangerous trait but how it interacts with other negative factors (such as aggression) determines how toxic and socially aversive it can become. Heym et al (2019) also found that narcissism is not problematic or dangerous as long as the other two traits (psychopathy and Machiavellianism) are not present in a person. Their research further indicated that traits of psychopathy and Machiavellianism are characterized by empathetic deficits but narcissism stands out as people with this trait do have some amount of empathy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, maintaining strong connections with society and the natural world appear key to alleviating negative affective and cognitive functioning (Caccioppo & Hawkley, 2009;Narvaez, 2013), which, when combined with findings of nature connectedness-related pro-social behaviour and greater agreeableness, empathy, and perspective-taking Passmore & Holder, 2017;Zhang, Piff, Iyer, Koleva, & Keltner, 2014), strikes a strong juxtaposition with the Hobbesian viewpoint that selfish and aggressive behavioural trends in westernised societies are normalised and considered 'adaptive'. Such traits account for some of the variation observed in so-called dark personalities (Heym et al, 2019;Lynam & Derefinko, 2006), which themselves can be considered adaptive in nature (Hall & Benning, 2006). Thus, exploring nature connectedness in relation to dark personalities may be of interest to researchers and clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher nature connectedness has been associated with pro-social behaviour, along with greater agreeableness, cognitive and affective facets of empathy, and perspective-taking Passmore & Sensitivity: Internal Holder, 2017; Zhang, Piff, Iyer, Koleva, & Keltner, 2014). These traits account for some of the variation observed in so-called dark personalities, commonly characterised by the dark triad (Heym et al, 2019;Lynam & Derefinko, 2006). Thus, exploring nature connectedness in relation to dark personalities may be of interest to researchers and clinicians.…”
Section: Introductionmentioning
confidence: 99%